Host resistance does not explain variation in incidence of male-killing bacteria in Drosophila bifasciata - Veneti, Zoe (BioMed Central, 2004)
BACKGROUND: Selfish genetic elements that distort the sex ratio are found widely. Notwithstanding the number of records of sex ratio distorters, their incidence is poorly understood. Two factors can prevent a sex ratio distorter from invading: inability of the sex ratio distorter to function (failure of mechanism or transmission), and lack of drive if they do function (inappropriate ecology for invasion). There has been no test to date on factors causing variation in the incidence of sex ratio distorting cytoplasmic bacteria. We therefore examined whether absence of the male-killing Wolbachia infection in D. bifasciata in Hokkaido island of Japan, in contrast to the presence of infection on the proximal island of Honshu, was associated with failure of the infection to function properly on the Hokkaido genetic background. RESULTS: The male-killer both transmitted and functioned well following introgression to each of 24 independent isofemale inbred lines carrying Hokkaido genetic backgrounds. This was maintained even under stringent conditions of temperature. We therefore reject the hypothesis that absence of infection is due to its inability to kill males and transmit on the Hokkaido genetic background. Further trap data indicates that D. bifasciata may occur at different densities in Hokkaido and Honshu populations, giving some credence to the idea that ecological differentiation could be important. CONCLUSIONS: The absence of the infection from the Hokkaido population is not caused by failure of the male-killer to function on the Hokkaido genetic background.